Qualitative Study Of Complementary Feeding For Stunting Toddlers Aged 13-24 Months In Cipadang Village, Pesawaran District - Sutrio Sutrio; Dewi Sri Sumardilah (JURNAL PROTEKSI KESEHATAN, 2020)
Stunting children are the result of chronic nutritional problems as a result of food quality, coupled with morbidity, infectious diseases and environmental problems. This study aims to determine the description of complementary feeding practice for stunting toddlers aged 13-24 months in Cipadang village. This study uses a qualitative approach conducted by conducting in-depth interviews and observations. The informants in this study were the main caregivers of toddlers's mother, family informants and health center nutrition workers. The results of the study showed that the parenting of breastfeeding complementary feeding was still less than the variation, portion and frequency of its giving. Mother or caregivers are encouraged to regularly come to the posyandu and ask cadres or health workers about the provision of good complementary feeding for stunting toddlers, especially in terms of portions, frequency and variation. In addition health workers must always provide assistance to stunting toddlers in order to get the optimal health degree.